RGS10 and RGS18 differentially limit platelet activation, promote platelet production, and prolong platelet survival - DeHelian, Daniel (Blood, 2020)
G protein–coupled receptors are critical mediators of platelet activation whose signaling can be modulated by members of the regulator of G protein signaling (RGS) family. The 2 most abundant RGS proteins in human and mouse platelets are RGS10 and RGS18. While each has been studied individually, critical questions remain about the overall impact of this mode of regulation in platelets. Here, we report that mice missing both proteins show reduced platelet survival and a 40% decrease in platelet count that can be partially reversed with aspirin and a P2Y(12) antagonist. Their platelets have increased basal (TREM)-like transcript-1 expression, a leftward shift in the dose/response for a thrombin receptor–activating peptide, an increased maximum response to adenosine 5′-diphosphate and TxA(2), and a greatly exaggerated response to penetrating injuries in vivo. Neither of the individual knockouts displays this constellation of findings. RGS10(−/−) platelets have an enhanced response to agonists in vitro, but platelet count and survival are normal. RGS18(−/−) mice have a 15% reduction in platelet count that is not affected by antiplatelet agents, nearly normal responses to platelet agonists, and normal platelet survival. Megakaryocyte number and ploidy are normal in all 3 mouse lines, but platelet recovery from severe acute thrombocytopenia is slower in RGS18(−/−) and RGS10(−/−)18(−/−) mice. Collectively, these results show that RGS10 and RGS18 have complementary roles in platelets. Removing both at the same time discloses the extent to which this regulatory mechanism normally controls platelet reactivity in vivo, modulates the hemostatic response to injury, promotes platelet production, and prolongs platelet survival.